In situ growing 3D-Cu coating to improve the reversibility and reaction kinetics of Zn metal anodes - Liang, Lianbao; Hang, Lifeng; Xie, Shuangcong; Men, Dandan; Jiang, Guihua; Chen, Yiyu (Frontiers in Chemistry, 2022)
The zinc metal anode is the most promising metal anode material in aqueous battery systems due to its low cost and high theoretical capacity. However, it still undergoes irreversible reactions such as premature failure of the dendrites/dead Zn during Zn stripping/plating, resulting in the inferior cycling stability of the Zn-based full cell. Here, we demonstrate a facile 3D-Cu alloy coating to improve Zn reversibility by providing spatial voids to accommodate the plated Zn to form dendrite-free morphology. Combining the larger 3D surface and the alloying–dealloying process, the Zn anode reactions exhibit enhanced reaction kinetics to meet large operating current densities. The 3D-Cu-coated Zn anode can deliver improved cycling stability for 350 h under a large areal capacity of 3 mAh cm−2. It also enables MnO2–Zn at the full cell level to achieve a specific capacity of 205 mAh g−1 and longer cycling for 350 cycles with 87.4% retention of the initial capacity. This research provides a new pathway to achieve high reversible Zn metal chemistry.